An investigation of what factors determine the way in which customer satisfaction is increased through omni-channel marketing in retail - Kamarin Merritt; Shichao Zhao (Administrative Sciences, 2020)
There have been significant changes evident across the retail sector over the last 20 years, which have been primarily influenced by technological advancements. These changes have forced many retailers to rethink their business models and utilise a combination of both brick and mortar stores and online domains to present an integrated shopping experience. In order to gain an understanding of how customer satisfaction is increased through omni-channel retailing, we collected data through survey research, specifically through semi-structured interviews and questionnaires. In order to generate concise and accurate findings, the data were analysed using thematic analysis. From this analysis, three themes were generated. The first theme explores the reasoning behind preferred shopping methods and what influences these customers' purchase methods. The second theme explores customers' personal preference and investigates the potential of using virtual reality as a method for increasing customer satisfaction. Finally, the third theme looks into utilising interactive technology to create a diversified user experience. This theme explores the potential of utilising a communication platform for customers and also designing a tangible interface for disabled customers. This study has opened up an opportunity for future research and has outlined potential design insights in how to improve customer experience and customer purchase intentions.
Keywords: 350; customer satisfaction; e-satisfaction; omni-channel retailing; value-sensitive design; thematic analysis (TA)